2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Occupational Safety and Health Act (OSHA) Hazard Communication Standard [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The purpose of the Occupational Safety and Health Act (OSHA) is to require certain employers to inform their employees of the dangers of hazardous chemicals. This is EDIS document FE409, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.